Carbon-nanostructured materials for energy generation and storage applications - Ndungu, P.; Nechaev, A.; Khotseng, L.; Onyegebule, N.; Davids, W.; Mohammed, R.; Vaivars, G.; Linkov, V. (South African Journal of Science, 2010)
We have developed and refined a chemical vapour deposition method to synthesise nanotubes using liquid petroleum gasasthe carbonsource. The nanotubes were thoroughly characterised by scanning electron microscopy, transmission electron microscopy X-ray diffraction and thermogravimetric analysis. The protocol to grow nanotubes was then adapted to deposit nanotubes on the surface of different substrates, which were chosen based upon how the substrates could be applied in various hydrogen energyconver-sion systems. Carbon nanotubes area nanostructured material with an extremely wide range of application sinvariousenergy applications. The methods outlined demonstrate the complete development of carbon nanotube composite materials with direct applications in hydrogen energy generation, storage and conversion.